Pengaruh Perbedaan Teknik Ekstraksi Tumbuhan terhadap Hasil Rendemen Mentol: Review - Nurlita, Rima; Mutya, Amallia Fitri Dewi; Hasanah, Uswatun (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2024)
One of the ingredients in essential oils is menthol. Menthol is a compound in the form of crystals that has a mint-like aroma, providing a refreshing cool sensation. Extraction of plants to produce menthol can be done using hydrodistillation, steam distillation and microwave extraction methods. The difference in extraction methods will also determine the menthol that will be produced. This review contains the differences in extraction methods for plants that produce the highest yield of menthol in quantity. The design method used in this review is a systematic review, where the data obtained is a collection of several related studies. From the search results, the hydrodistillation method produced an average yield of menthol from the 5 sources of 58.09%, the steam distillation extraction method was 54.7%, and the microwave extraction was 28%. So the hydrodistillation method produces the largest yield of menthol in quantity compared to the steam distillation and microwave extraction methods.